Pension Reform in the Baltics, Russia, and other Countries of the Former Soviet Union (BRO). (IMF Working Papers; Working Paper ;, 1998)
Despite their increasing fiscal burden, the public pension systems of BRO countries are failing to provide adequate social protection. Although there is a broad consensus about the need for pension reforms, BRO countries are debating whether to embark on systemic reforms or whether to correct the distortions in their pay-as-you-go (PAYG) pension systems. The paper reviews the measures taken by BRO countries during the transition period to address their pension problems and examines the options for further reform. It makes a strong case for a gradual reform approach aimed at establishing a multi-pillar system over the long run, but initially focused on implementation of 'high-quality' reforms of the PAYG system.